A Brief Account on Protozoan Infection in Asian Stinging Catfish, Heteropneustes Fossilis (Bloch, 1794) In Different Seasons of Bangladesh (Dhaka University Journal of Biological Sciences, 2023)
The study was conducted to identify the protozoan parasites in a freshwater indigenous air breathing fish, Heteropneustes fossilis (Bloch, 1794). The host fish was collected during mid of the April 2018 to end of the March 2019 from freshwater bodies of Mymensingh, Kishoregonj, Faridpur, Jashore, Manikganj and Bogura districts of Bangladesh. Three species of phylum myxozoa namely Henneguya singhi, Henneguya qadrii, Henneguya mystusia, one species of phylum ciliophora namely Trichodina siddiquae and two species of phylum mastigophora namely Trypanosoma singhii and Piscinoodium pillulare were identified in H. fossilis. The parasites of all infected hostswere observed in gill, body slime and blood, however gillswere commonly infected by parasites rather than body slime and blood. Three species of parasite Piscinoodium pillulare, Henneguya qadrii and Henneguya mystusia were first recorded in this host fish and novel locality record in Bangladesh. H. fossilis was found to be infected over the three major (p